Integral Education Based on the Pedagogy of Unity - Mariola Teresa Kozubek (Vasyl Stefanyk Precarpathian National University, 2023)
The article substantiates the opinion that integral education based on personalism covers all dimensions of personality development: physical, mental, social, cultural, and religious. The purpose of the study is to present the innovative content of integral education, expressed in the Pedagogy of unity by Chiara Lubich. The reflections on integral education, based on the interpretation of Lubich's texts and the experience of the Focolare Movement educational community, founded by her, describe the original directions of integral education in the Pedagogy of unity. It is emphasized that the concept of holistic education of the Pedagogy of unity, based on Christian ideas, is compatible with the trends of personalistic pedagogy and - although it originates from the religious message of the charism of unity by Chiara Lubich - is characterized by universality, developed on love, presenting it as a pedagogical value. Based on the results of the analysis of modern scientific sources, it has been proven that due to love, and mutual understanding in interpersonal relationships, effective communication is created at the social level, a person is elevated to higher spiritual values, and a harmonious educational environment is formed for self-assertion and freedom. It has been found that this direction of education makes it possible to build universal fraternity, peace, and unity. The author claims that the interpretation of holistic education in this context allows for preserving the unity of the human being and his/her harmonious development. The presented analysis of the features of integrated education by the pedagogy of unity does not diminish the general idea expressed in Chiara Lubich's theory. New directions have been determined for further scientific research, both in the field of the hermeneutics of Lubich's works as well as in the field of scientific research of the educational practice of the Focolare Movement and educational institutions in various cultures of the world, oriented on the charism of unity.